(untitled) (Comparative & International Education Series, 2023)
Amazing Nepali Women Writers introduces young readers to 15 extraordinary women writers who have made a significant impact in Nepali literature. Perfect for elementary school students, this collection celebrates the incredible talents of Nepali women writers– poets, novelists, and authors who have contributed to the rich literary heritage of Nepal. Each trailblazing woman has her own unique voice and inspiring story to share. This book highlights their accomplishments and also serves as an inspiration to young readers, empowering them to believe in their own dreams and capabilities. Let their words spark your imagination and fuel your passion for writing as you explore the captivating world of Nepali literature through the eyes of these remarkable female authors. Cover Design: Sahar Aghasafari